Citizenship in Early Modern China. A Commentary to Maarten Prak, Citizens Without Nations: - Moll-Murata, Christine (TSEG - The Low Countries Journal of Social and Economic History, 2020)
This article comments on the discussion of pre-modern Chinese citizenship in Maarten Prak’s Citizens without Nations. It confirms the conclusion drawn by Prak that many elements of European citizenship were also present in China, but raises questions about two aspects: the presumed absence of formal citizenship in China and the position of Chinese cities within a national administrative structure. On the first of these points the article shows that formal civilian status implied rights such as the protection of person and property in China as well as in Europe. On the second issue, it demonstrates that the authorities in Chinese cities, especially in periods when state power was relatively weak, depended on cooperation with self-organized local institutions, and that these also included organizations for self-defense.